(untitled) (Al-Jabal Journal of Humanities and Applied Sciences, 2024)
The idea of ​​consumer protection has grown as a result of the development witnessed in contemporary life, the openness of markets, and the spread of poor goods and services. Therefore, it became a subject of interest to legislators in all countries, and a fertile field for research and diligence. Scientific forums were organized regarding it, and its own associations and organizations were established. The Libyan legislator, like other legislators, was interested in this idea, so he criminalized some of its forms and assigned it to criminal penalties in the Penal Code. He also devoted to it Chapter Two of Book Eleven of the Commercial Activity Law No. 23 of 2010 AD with the aim of ensuring the integrity of economic transactions and the safety of products, and verifying the extent to which It conforms to the approved standards and specifications, and the idea of ​​issuing a special consumer protection law has not yet occurred to him.However, all of this has not yet reached effective consumer protection due to the development of its concept and the development of its means of protection. Consumer protection is no longer limited to creating guarantees to provide good goods and preventing monopoly, but rather it has become a new concept that leads to the destabilization of some established rules in civil law and the law of civil and commercial procedures. Due to the nature of the consumer relationship based on variation and difference in legal positions, there are many stable rules in these two laws that limit the desired protection for consumers, as this protection can only be achieved by developing and adapting them. In this paper, we attempt to touch upon some of these rules in the two aforementioned laws by analyzing them, stating the views of jurisprudence regarding them, pointing out their shortcomings, and proposing their development in a way that serves the idea of ​​consumer protection, by following the analytical scientific research method, in accordance with a research plan of three demands: (First), In it, we define the concept of the consumer, (secondly), we present some rules of civil law that limit consumer protection, (thirdly), we present some rules of the Civil Procedure Code that limit consumer protection. We conclude this with a conclusion that includes the most important results and recommendations.